Pengaruh Pengawasan dan Komunikasi Internal Terhadap Kepuasan Kerja Serta Dampaknya Terhadap Kinerja Pegawai Dinas Pekerjaan Umum dan Penataan Ruang Provinsi Riau - Wildayana Wildayana; Machasin Machasin; Yulia Efni (Bahtera Inovasi, 2019)
This study aims to determine the effect of supervision and internal communication on performance through employee job satisfaction in the Department of Public Works and Spatial Planning of Riau Province.The population were all employees of echelon II, III and IV as big as 138 people and the size of sample is as many as 103 people. The technique of determining the sample is by using purposive sampling. The path analysis is used to analyze the collected data.The results of the study indicate that: (1) supervision influences employee’s job satisfaction, (2) internal communication contributes positively on employee’s job satisfaction, (3) supervision correlates significantly with employee’s performance, (4) internal communication influences employee’s performance, (5) supervision and Internal communication affect positively to performance through job satisfaction.